Framework vs. side-chain amphidynamic behaviour in oligo-(ethylene oxide) functionalised covalent-organic frameworks. Issue 50 (6th June 2018) - Vazquez-Molina, Demetrius A.; Pope, Giovanna M.; Ezazi, Andrew A.; Mendoza-Cortes, Jose L.; Harper, James K.; Uribe-Romo, Fernando J.
Abstract : We designed and synthesized crystalline covalent-organic frameworks that exhibit both slow and fast molecular motions in their structure. Abstract : We present a family of covalent organic frameworks that have been functionalized with oligo-(ethylene oxide) chains of varying lengths. Because of the open structure of the COFs, the side chains do not interfere with their crystallization obtaining materials with predictable crystal structure. The difference in length of the side-chains allowed for the determination of amphidynamic behaviour with the use of 13 C solid-state NMR relaxation methods. Computational calculations further contribute to understanding the atomistic dynamic behaviour of the different atoms. This study demonstrates the ability to design complex behaviour in organic crystals.